Coronary Plaque Characteristics in Hemodialysis-Dependent Patients as Assessed by Optical Coherence Tomography - Chin, Chee Yang; Matsumura, Mitsuaki; Maehara, Akiko; Zhang, Wenbin; Lee, Cheolmin Tetsumin; Yamamoto, Myong Hwa; Song, Lei; Parviz, Yasir; Jhalani, Nisha B.; Mohan, Sumit; Ratner, Lloyd E.; Cohen, David J.; et al. (The American journal of cardiology, 2017)
Coronary arteries in patients with chronic kidney disease (CKD) have been shown to exhibit more extensive atherosclerosis and calcium. We aimed to assess characteristics of coronary plaque in hemodialysis (HD)-dependent patients using optical coherence tomography (OCT). This was a multicenter, retrospective study of 124 patients with stable angina who underwent OCT imaging. Sixty-two HD-dependent patients who underwent pre-intervention OCT for coronary artery disease were compared 1:1 with a cohort of patients without CKD, matched for age, diabetes mellitus, gender, and culprit vessel. Baseline characteristics were comparable. Pre-intervention OCT imaging identified 62 paired culprit, 53 paired non-culprit, and 19 paired distal vessel lesions. Lesion length, minimum lumen area, and area stenosis were similar between groups. The HD-dependent group had greater mean calcium arcs in culprit (54.3° vs 26.4°, p = 0.004) and non-culprit lesions (34.3° vs 24.5°, p = 0.02) and greater maximum calcium arc in distal vessel segments (101.6° vs 0°, p = 0.03). There were no differences in lipid arcs between groups. There was a higher prevalence of thin intimal calcium, defined as an arc of calcium >30° within intima <0.5 mm thick, in patients in the HD-dependent group (41.9% vs 4.8%, p <0.001). There was a higher prevalence of calcified nodules in the HD-dependent group (24.2% vs 9.7%, p = 0.049) but no differences in medial calcification or thin-cap fibroatheroma. In conclusion, in this OCT study, HD-dependent patients, compared with matched patients without CKD, had more extensively distributed coronary calcium and uniquely, a higher prevalence of non-atherosclerotic thin intimal calcium. This thin intimal calcium may cause an overestimation of calcium burden by intravascular ultrasound and may contribute to the lack of correlation between increased coronary artery calcification scores with long-term outcomes in patients with CKD.